ANALISIS PERBANDINGAN UNIT TEST AUTOMATION FRAMEWORK DENGAN METODE THE DISTANCE TO THE IDEAL ALTERNATIF - Fakhrii, Rifaldi; Setiani, Novi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This Study aims to analyze and compare four unit test automation frameworks, namely EvoSuite, Randoop, Squaretest, and Github Copilot, using the Distance to Ideal Alternative(DIA) method. The four frameworks were evaluated based on three main parameters, Technical Economic View, Testing Process View, and Quality Standard View. The DIA method was chosen because of its advantage in providing more consistent results by calculating the distance to positive and negative ideal alternative solutions. This research collects data through questionnaires distributed to developers who have experience in the unit testing program. The result showed that Github Copilot occupies the best position in almost all aspects, especially in programming language flexibility and ease of use. However, it has a weakness in subscription fees. The results of this study are expected to guide software developers in choosing a test automation framework that suits their needs, both from a technical economic perspective, as well as increase the literature related to the performance and effectiveness of unit testing tools in software development.